Agriculture in the Karakum: An archaeobotanical analysis from Togolok 1, southern Turkmenistan (ca. 2300–1700 B.C.) - Billings, Traci N.; Cerasetti, Barbara; Forni, Luca; Arciero, Roberto; Dal Martello, Rita; Carra, Marialetizia; Rouse, Lynne M.; Boivin, Nicole; Spengler, Robert N. (Frontiers in Ecology and Evolution, 2022)
Southern Central Asia witnessed widespread expansion in urbanism and exchange, between roughly 2200 and 1500 B.C., fostering a new cultural florescence, sometimes referred to as the Greater Khorasan Civilization. Decades of detailed archaeological investigation have focused on the development of urban settlements, political systems, and inter-regional exchange within and across the broader region, but little is known about the agricultural systems that supported these cultural changes. In this paper, we present the archaeobotanical results of material recovered from Togolok 1, a proto-urban settlement along the Murghab River alluvial fan located in southeastern Turkmenistan. This macrobotanical assemblage dates to the late 3rd - early 2nd millennia B.C., a time associated with important cultural transformations in southern Central Asia. We demonstrate that people at the site were cultivating and consuming a diverse range of crops including, barley, wheat, legumes, grapes, and possibly plums and apples or pears. This, together with the associated material culture and zooarchaeological evidence, suggest a regionally adapted mixed agropastoral economy. The findings at Togolok 1 contribute to the ongoing discussion of dietary choices, human/landscape interactions, and the adaptation of crops to diverse ecosystems in prehistoric Central Asia.